A rare case of arteriovenous malformation following hysterectomy in a case of choriocarcinoma - R, Suchitra; P, Manjunath; Taj, Shameem; Kalla, Radhika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A uterine arteriovenous malformation (AVM) is a rare cause of uterine bleeding. It may have varied presentations ranging from being completely asymptomatic; to features of congestive heart failure, to vaginal bleeding which may at times life be threatening. Clinical findings in such cases are often un-reliable; requiring a high index of suspicion to make the diagnosis. We report a case of a 46-year-old lady who presented with heavy vaginal bleeding. She has undergone hysterectomy with a histopathology of choriocarcinoma one and half months back. She has received chemotherapy and 8 fractions of radiotherapy for the same. AVM was diagnosed following a CT angiogram and was managed by embolization. We also discuss in brief about this uncommon but serious condition which the radiologist/gynaecologist may encounter in their practice. AV Malformation is a rare but potentially life-threatening cause of vaginal bleeding which must be kept in the differential diagnosis of sudden and massive vaginal bleeding. It requires a high index of clinical suspicion. Despite its rarity, early recognition of an AVM is imperative to enable timely diagnosis and intervention.